Transit Stations Sub-centers in Rotterdam Zuid - Yagiz, Söylev; Yang, Zhang; Triggianese, Manuela; Veloso e Zarate, Halina (City of Innovations, 2022)
The book is the result of the course 'City of Innovations Project' at TU Delft Faculty of Architecture and the Built Environment, led by the group of Complex Projects at the Department of Architecture. 'Transit stations: sub-centres in Rotterdam Zuid' is the theme of the course running in spring 2022. It is connected to the research project Walk-In (acronym of Widening sustAinable mobiLity networKs: Impact on Nodes) financed by NWO and part of the KIEM GoCi program. Students presented their research and design scenarios to the project partners in April 2022 and they learned from their expertise throughout the course. Those are the City of Rotterdam, Delta Metropool Association, De Zwarte Hond, PosadMaxwan, Mecanoo, Bureau Spoorbouwmeester, I&M, Prorail with the collaboration of the University of Gustave Eiffel. By doing so, students contributed to the objective of Walk-In: to investigate the potential of suburban stations in transition in the context of the low car inner city of Rotterdam and to develop generic guidelines and spatial solutions for the integration of sustainable mobility with public space and mixed urban functions and services.